2017
DOI: 10.17586/2220-8054-2017-8-1-48-58
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator (fermion-boson)-crossover origin of pseudogap phase of cuprates I: anomalous heat conductivity, insulator resistivity boundary, nonlinear entropy

Abstract: Among all the experimental observations of cuprate physics, the metal-insulator-crossover (MIC), seen in the pseudogap (PG) region of the temperature-doping phase diagram of copper-oxides under a strong magnetic field when the superconductivity is suppressed, is most likely the most intriguing one. Since it was expected that the PG-normal state for these materials, as for conventional superconductors, is conducting. This MIC, revealed in such phenomena as heat conductivity downturn, anomalous Lorentz ratio, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…[6]) we have shown that these non-Landau Fermi liquid behaviors of the low-T heat conductivity and Lorentz ratio are results of the MIC property of the cuprate PG regions, in which the IGS originates from a plasmon gas of 2D charged single bosons, pinned by a ferroelectric field of parent compound atoms (see also previous section). In this section, we show that the downturn T dependence carries the important information on the low-T scale of the MIC charge conductivity or resistivity.…”
Section: Resistivity Temperature Upturnmentioning
confidence: 70%
See 4 more Smart Citations
“…[6]) we have shown that these non-Landau Fermi liquid behaviors of the low-T heat conductivity and Lorentz ratio are results of the MIC property of the cuprate PG regions, in which the IGS originates from a plasmon gas of 2D charged single bosons, pinned by a ferroelectric field of parent compound atoms (see also previous section). In this section, we show that the downturn T dependence carries the important information on the low-T scale of the MIC charge conductivity or resistivity.…”
Section: Resistivity Temperature Upturnmentioning
confidence: 70%
“…Then, the bosonic insulator -bosonic metal transition can experimentally be observed at a point for this frequency when it goes to zero. Physically, this transition corresponds to the changing of the charged boson gas elementary excitation spectrum from a plasmon part into a free particle one [6].…”
Section: Nematicity Igs Nematicity-stripe Phases Transition and Fementioning
confidence: 99%
See 3 more Smart Citations